0861 Age, Race, And Continuous Positive Airway Pressure (CPAP) Confidence Score At 1-week Predict 3-month CPAP Adherence In Older Adults With Amnestic Mild Cognitive Impairment And Moderate To Severe Obstructive Sleep Apnea. (27th May 2020) - Richards, K C; Vallabhaneni, V; Moelter, S; Davis, E M; Morrison, J; Lozano, A; Hanlon, A; Wang, Y; Wolk, D; Gooneratne, N
Abstract: Introduction: Adherence to continuous positive airway pressure (CPAP) may delay cognitive decline in older adults with obstructive sleep apnea (OSA) and amnestic mild cognitive impairment (MCI), defined as deficits in memory that do not significantly impact daily functioning. The aim of this analysis was to identify predictors of CPAP adherence in this population. Methods: Data are from Memories 2, an ongoing multisite clinical trial on the effect of treatment of moderate to severe OSA on cognitive decline in older adults 65-85 years of age who have amnestic MCI. Unadjusted and adjusted linear models were used to examine predictors of mean hours of CPAP use at 3 months. Predictors were age, sex (male/female), race (White/Non-White), education (more than high school, less than high school), Apnea-hypopnea index (AHI), Epworth Sleepiness Scale (ESS), and CPAP Comfort and Confidence scores at 7 days. Collinearity in the adjusted model for CPAP use at 3 months was examined using the variance inflation factor. Results: Of 57 participants, most were male (54%), White (72%), with a mean age of 66.3 years (SD: 6.1). Mean AHI in this sample was 35.1 (SD: 19.9), with mean daily hours of CPAP use at 3 months 5.3 hours (SD: 2.3). Adjusted linear model results demonstrated that younger age (β=-0.13, SE=0.04, p=0.0032), White race (β=2.56, SE=0.58, p<0.0001), and higher 7-day CPAP Confidence score (β=0.48, SE=0.17, p=0.0086) were significantly associated with CPAP use at 3 months. Sex, education, AHI, ESS, and CPAP comfort were not statistically significant predictors of adherence. Conclusion: Tailored interventions to increase self-efficacy during the first 7 days of CPAP treatment, especially in Non-Whites and those older than 74 years, may improve long-term CPAP adherence in older adults with amnestic MCI. Support: R01AG054435